ALIRAN-ALIRAN DALAM TASAWUF - Andariati, Leni (STIT Sunan Giri Bima, 2020)
The journey of sufism its inception until today has experience various phases. This is indicated that sufism is not something obsolete, because it is able to adjust the development of this time without losing essential meaning. This article looks at the phases of defelopment in sufism from its inception to the present day, in addition it also dicusses the currents from sufism. This research was conducted with qualitative methods, the sources obtained from various of books, articles, and journals that accordance with the objek of research. This article found that sufism developed thrugh five phases, it is phases of formation, development, consolidation, philosophy, and purification phases. Each phases there is some character, so each character has a different style. The existence of these differences gave two streams in sufism, namely is semi-philosophy (falsafi) and Sunni sufism. Semi-philosopical sufism is characterized by syathahiyat, ehich a sufi experiences a spiritual drunkenness or ecstasy. And the sufis in sunni sufism are either conscious or not experiencing ecstasy.